RADIKALISME ISLAM VS MODERASI ISLAM: UPAYA MEMBANGUN WAJAH ISLAM INDONESIA YANG DAMAI - Nurul Faiqah; Toni Pransiska (AL-FIKRA, 2018)
This article explains that all religions strictly prohibit acts of terror that can threaten harmony, wholeness and diversity of the nation. Terrorism and radicalism are not always ideologically motivated, but non-religious factors are dominant such as social, economic, political and others. Therefore, it is necessary to promote and promote a new discourse and paradigm of inclusive and tolerant Islamic understanding of moderation of Islam (wasathiyah al-Islām). The emergence of radical Islamism must immediately be balanced with the vision of moderate Islam. That is the image of Islam that upholds the valuesof moderation, tolerance and equality of rights.Moderation of Islam is a middle ground in the midst of religious diversity. The image of moderation of Islam appears in harmony between Islam and local wisdom. This Local Value as a cultural heritage of the archipelago, can be juxtaposed parallel so that between the spirit of Islam and cultural wisdom goes hand in hand, not mutually negate. This is where the image of Indonesian Islam is considered very appropriately applied in the context of cultural heterogeneity in the ASEAN region and the world